The age of agile how smart companies are transforming the way work gets done - Denning, Stephen (New York AMACOM, 2018)
More value from less work. An unstoppable business revolution is under way-and it is Agile. Companies that embrace Agile Management learn to connect everyone and everything . . . all the time. They can deliver instant, intimate, frictionless value on a large scale. Agile began emerging many decades ago, but truly took off in the software development industry. Sparking dramatic improvements in quality, innovation, and speed-to-market, the Agile movement is now spreading quickly throughout all kinds of companies. It enables a team, a unit, or an enterprise to nimbly adapt and upgrade products and services to meet rapidly changing technology and customer needs. And the process is applicable anywhere-companies don't need to be born Agile, like Spotify. Even centuries-old Barclays is making the transition and reaping rewards. Filled with examples from every sector, The Age of Agile helps readers: Master the three laws of Agile Management (team, customer, network) * Embrace the new mindset * Overcome constraints * Employ meaningful metrics * Make the entire organization Agile * And more With this breakthrough approach, even global giants can learn to act entrepreneurially. Their future depends on it.
Includes index.
Keywords: Organizational effectiveness